Evaluation of dimensional accuracy, flexural strength and surface roughness of 3D-printable denture base resin modified with different concentrations of cerium oxide nanoparticles: a comparative in-vitro study - Ibrahim A. Mohamed; Mohamed sherine El Attar; Sonia M. El Shabrawy; Eman Zaghloul Alrafah (BMC Oral Health)
Abstract Background Low antimicrobial activity is a major drawback of three-dimensional (3D) printed denture bases, so the incorporation of antimicrobial nanoparticles possesses an effective antifungal and antibacterial effect. However, it is important to assess the outcome of adding such nanofillers on the dimensional accuracy, flexural strength, and surface roughness of 3D-printed denture bases. This in vitro study aimed to evaluate dimensional accuracy, flexural strength, elastic modulus, and surface roughness of 3D printed denture base resin modified with different concentrations of cerium oxide nanoparticles as an antimicrobial agent. Methods A total sample of (N = 72) was 3D printed as Cerium oxide particles were mixed with the denture base resin to acquire these groups: Group I (control) with no nanoparticles (N = 24), Group II with 0.5 wt.% cerium oxide nanoparticles (N = 24), and Group III with 1 wt.% cerium oxide nanoparticles (N = 24). The printed samples (N = 72) were tested for printing accuracy by a digital caliper, and flexural strength (n = 12) with a universal testing machine, while Surface roughness (n = 12) was assessed by a profilometer. For data analysis, One and 2-Way ANOVA, followed by Tukey post hoc, and the Kruskal Wallis test followed by the Dunn post hoc test were used with Bonferroni correction (P ≤ .05). Results Regarding printing accuracy specimens there was a statistically significant deviation between the control group and the 1% cerium oxide group in length and width percent error (%). there was no significant effect on flexural strength in all the groups. The 1% Cerium Oxide group recorded the highest mean values. There was a significant difference among all groups of surface roughness before polishing; the control group had the highest mean values. After polishing there was no significant effect. Conclusions Regarding printing dimensional accuracy, the 0.5% cerium oxide group had no significant deviation in the printed specimens, while the 1% group had a significant deviation regarding the length and width dimensions of the specimens. The addition of cerium oxide led to a slight improvement in the flexural strength and elastic modulus of the 3D-printed resin without a significant amount. The polishing process of the modified specimens is required to enhance the surface roughness of the material.